2018
DOI: 10.1002/jcb.26889
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA SNHG14 contributes to gastric cancer development through targeting miR‐145/SOX9 axis

Abstract: This study aimed to elucidate the roles of long non-coding RNA SNHG14 in gastric cancer development. LncRNA SNHG14 was markedly up-regulated in gastric cancer tissues and cells. Knockdown of SNHG14 significantly inhibited SGC-7901 cell viability, migration, invasion, and promoted cell apoptosis. In addition, miR-145 was negatively regulated by SNHG14 and the effects of SNHG14 knockdown on cell viability, apoptosis, migration, invasion, and the expression of apoptosis-related proteins and EMT-markers were rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 35 publications
5
56
0
Order By: Relevance
“…Sox9 transcriptionally activates LASP-1 expression to increase cell proliferation, migration, and invasion in lung cancer [ 22 ]. Recent studies demonstrated that lncRNAs act as competitive endogenous RNA (ceRNA) to post-transcriptionally regulate Sox9 expression, such as SNHG14 and MALAT1 [ 23 , 24 ]. However, to date, whether lncRNAs are involved in the post-translational modification of Sox9 protein remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sox9 transcriptionally activates LASP-1 expression to increase cell proliferation, migration, and invasion in lung cancer [ 22 ]. Recent studies demonstrated that lncRNAs act as competitive endogenous RNA (ceRNA) to post-transcriptionally regulate Sox9 expression, such as SNHG14 and MALAT1 [ 23 , 24 ]. However, to date, whether lncRNAs are involved in the post-translational modification of Sox9 protein remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…miR-511 inhibits the activation of the PI3K/Akt signaling pathway in breast cancer cells by targeting SOX9. SOX9 participates in the regulation of the PI3K/Akt signaling pathway (30,31); thus, whether miR-511 inactivates PI3K/Akt signaling in breast cancer cells was examined. To test this hypothesis, western blot analysis was performed to detect the molecules associated with the PI3K/Akt pathway in MCF-7 and MDA-MB-231 cells following co-transfection with miR-511 mimics and pcDNA3.1 or pcDNA3.1-SOX9.…”
Section: Sox9 Expression Is Negatively Correlated With Mir-511 Expresmentioning
confidence: 99%
“…GAS5 has been proved to regulate cardiac fibroblast activation and fibrosis [11]. In addition, SNHG14 was reported to contribute to cell proliferation of gastric cancer cells through miR-145/SOX9 axis [12]. Recently, long intergenic non-protein coding RNA 511 (LINC00511) was widely reported in multiple tumors.…”
Section: Introductionmentioning
confidence: 99%